2017
DOI: 10.1111/pde.13113
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Flares in Children with Atopic Dermatitis with Regular Use of an Emollient Containing Glycerol and Paraffin: A Randomized Controlled Study

Abstract: Regular emollient use in children with mild to moderate AD reduces flares and corticosteroid consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 25 publications
1
43
0
2
Order By: Relevance
“…The efficacy of emollient creams in reducing xerosis in children with AD has been described previously described . Importantly, treating xerosis improves quality of life in these patients and reduces flares as well as topical corticosteroid consumption . In agreement with these observations, the use of emollient creams is recommended by treatment guidelines …”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…The efficacy of emollient creams in reducing xerosis in children with AD has been described previously described . Importantly, treating xerosis improves quality of life in these patients and reduces flares as well as topical corticosteroid consumption . In agreement with these observations, the use of emollient creams is recommended by treatment guidelines …”
Section: Discussionmentioning
confidence: 57%
“…Primary efficacy results, measured at study completion (i.e. after 12 weeks of treatment), have been already published elsewhere and demonstrated that the regular use of an emollient prevents flares in children with AD . In the present report, we analysed the kinetics of the response over 12 weeks of treatment with these two emollients.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations